Broccoli stem extract enhances browning inhibition in fresh-cut peach fruit by inhibiting polyphenol oxidase activity and improving antioxidant capacity - Zhang, Fengru; Jiang, Shu; Jia, Shuang; Gui, Boya; Wei, Yingying; Chen, Yi; Ye, Jianfen; Xu, Feng; Ding, Phebe; Shao, Xingfeng (Elsevier B.V., 2025)
This study focused on the anti-browning effect of broccoli stem extract (BE) on fresh-cut peaches. Compared to L-cysteine (L-Cys), BE showed the higher inhibition of the surface browning in fresh-cut peach fruit. This was accompanied with a more decreased polyphenol oxidase (PPO) activity and down-regulation of PpPPO expression. BE showed a non-competitive inhibition for peach PPO, and the highest inhibition rate (85.23 ± 3.86 %) was found when PPO catalyzed the oxidation of catechol. Furthermore, sulfur-containing compounds, including methylthiouracil (MTU), S-Methyl methanethiosulfonate (MMTS) and thiophene, 2-propyl- were identified in BE and shown to inhibit PPO activity. The molecular docking also indicated that these three compounds spontaneously bound PPO via hydrogen bonding, π-π conjugation and hydrophobic interactions, resulting in the PPO inhibition and its associated browning. BE also increased the total phenol and flavonoids content as well as antioxidant capacities in fresh-cut fruit, suggested by increased activities of catalase (CAT), ascorbate peroxidase (APX) and 2, 2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) free radical scavenging rate. Therefore, BE could be a natural anti-browning agent that can be used for the inhibition of PPO-initiated discoloration in peach fruit.